Identification of LPS-Activated Endothelial Subpopulations With Distinct Inflammatory Phenotypes and Regulatory Signaling Mechanisms - Dayang, Erna-Zulaikha; Plantinga, Josée; ter Ellen, Bram; van Meurs, Matijs; Molema, Grietje; Moser, Jill (Frontiers in Immunology, 2019)
Sepsis is a life-threatening condition caused by a dysregulated host response to infection. Endothelial cells (EC) are actively involved in sepsis-associated (micro)vascular disturbances and subsequent organ dysfunction. Lipopolysaccharide (LPS), a Gram-negative bacterial product, can activate EC leading to the expression of pro-inflammatory molecules. This process is molecularly regulated by specific receptors and distinct, yet poorly understood intracellular signaling pathways. LPS-induced expression of endothelial adhesion molecules E-selectin and VCAM-1 in mice was previously shown to be organ- and microvascular-specific. Here we report that also within renal microvascular beds the endothelium expresses different extents of E-selectin and VCAM-1. This heterogeneity was recapitulated in vitro in LPS-activated human umbilical vein EC (HUVEC). Within 2 hr after LPS exposure, four distinct HUVEC subpopulations were visible by flow cytometric analysis detecting E-selectin and VCAM-1 protein. These encompassed E-selectin-/VCAM-1- (-/-), E-selectin+/VCAM-1- (E-sel+), E-selectin+/VCAM-1+ (+/+), and E-selectin-/VCAM-1+ (VCAM-1+) subpopulations. The formation of subpopulations was a common response of endothelial cells to LPS challenge. Using fluorescence-activated cell sorting (FACS) we demonstrated that the +/+ subpopulation also expressed the highest levels of inflammatory cytokines and chemokines. The differences in responsiveness of EC subpopulations could not be explained by differential expression of LPS receptors TLR4 and RIG-I. Functional studies, however, demonstrated that the formation of the E-sel+ subpopulation was mainly TLR4-mediated, while the formation of the +/+ subpopulation was mediated by both TLR4 and RIG-I. Pharmacological blockade of NF-κB and p38 MAPK furthermore revealed a prominent role of their signaling cascades in E-sel+ and +/+ subpopulation formation. In contrast, the VCAM-1+ subpopulation was not controlled by any of these signaling pathways. Noteworthy is the existence of a ‘quiescent’ subpopulation that was devoid of the two adhesion molecules and did not express cytokines or chemokines despite LPS exposure. Summarizing, our findings suggest that LPS activates different signaling mechanisms in EC that drive heterogeneous expression of EC inflammatory molecules. Further characterization of the signaling pathways involved will enhance our understanding of endothelialheterogenic heterogeneous responses to sepsis related stimuli and enable the future design of effective therapeutic strategies to interfere in these processes to counteract sepsis-associated organ dysfunction.